2022
DOI: 10.1021/acsami.2c11131
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell Osteogenesis and Osteoimmunology Regulated by Piezoelectric Biomaterials with Controllable Surface Potential and Charges

Abstract: Bone regeneration is a well-orchestrated process involving electrical, biochemical, and mechanical multiple physiological cues. Electrical signals play a vital role in the process of bone repair. The endogenous potential will spontaneously form on defect sites, guide the cell behaviors, and mediate bone healing when the bone fracture occurs. However, the mechanism on how the surface charges of implant potentially guides osteogenesis and osteoimmunology has not been clearly revealed yet. In this study, piezoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…In a previous study, the surface of titanium implants was modified with divalent cations and macrophage polarization toward the M2 phenotype was significantly enhanced ( Lee et al, 2016 ). Mao et al (2022) further evaluated the effect of material surface charge on macrophages and bone regeneration. Scaffold with positive surface charges significantly inhibited M1 polarization of macrophages and enhanced osteogenic differentiation of MSCs.…”
Section: Biomaterials Design and Macrophage Regulationmentioning
confidence: 99%
“…In a previous study, the surface of titanium implants was modified with divalent cations and macrophage polarization toward the M2 phenotype was significantly enhanced ( Lee et al, 2016 ). Mao et al (2022) further evaluated the effect of material surface charge on macrophages and bone regeneration. Scaffold with positive surface charges significantly inhibited M1 polarization of macrophages and enhanced osteogenic differentiation of MSCs.…”
Section: Biomaterials Design and Macrophage Regulationmentioning
confidence: 99%
“…Among all energy sources, mechanical energy is widely available in our daily lives either from human motions such as walking and running or from nature such as water flow, vibrations, and so on. To harvest these mechanical energies, self-powered systems based on piezoelectric materials have been developed, which can generate electric fields in response to small mechanical deformations such as cell movements, body motions, or external stimulation, to regulate the membrane voltage and ion channel activity of immune cells. Piezoelectric materials are noncentrosymmetric in nature, which undergo deformation when subjected to external force and lead to piezoelectric polarization, resulting in electric charge generation across the edges. Electrical stimulation based on piezoelectric materials such as poly- l -lactic acid (PLLA), barium titanate (BaTiO 3 ), polyvinylidene fluoride (PVDF), etc.…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
“…Moreover, an enhanced immunomodulatory effect was observed with positively charged piezoelectric materials compared to their negative counterparts. Mao et al in 2022 showed that positive charges on BaTiO 3 /β-TCP (BTCP) favored the transition of macrophages toward the M2 phenotype which reduced the local inflammatory response and facilitated osteogenesis. BTCP+ and BTCP– were developed by orienting the polarization in the opposite direction, and their surface potentials were measured to be +107 and −175 mV, respectively .…”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of electroactive materials and, in particular piezoelectric ones, for the electrical stimulation of cell cultures and tissues has been proposed. Among them, poly­(vinylidene fluoride) (PVDF) and its co-polymers stand out due to their highest piezoelectric coefficient (d 33 ) and their possibility to be processed in a large variety of tailored morphologies and microstructures. , Depending on the processing conditions, semicrystalline PVDF can be obtained in five different crystalline phases, known as α, β, γ, ε, and δ, , being the β-phase the most electroactive one. In addition, the dipole moments of the β-phase PVDF can be aligned by the application of an electric field.…”
Section: Introductionmentioning
confidence: 99%